2022
DOI: 10.3389/fpsyg.2022.835200
|View full text |Cite
|
Sign up to set email alerts
|

Personality Styles of Dentists Practicing Hypnosis Confirm the Existence of the Homo Hypnoticus

Abstract: Several publications with healthcare professionals, such as psychotherapists, have shown a significant difference in personality styles in practitioners using hypnosis compared to those not using hypnosis. To investigate differences in personality styles, dentists were contacted to participate in a personality-inventory [Personality Style and Disorder Inventory (PSDI)] online survey. Dentists using hypnosis (HYP DGZH) (n = 418) were compared to dentists not using hypnosis (NONHYP DENT) (n = 162). Results show … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Whether the normal distribution (10–25% highly hypnotizable, 10–25% low hypnotizable and the rest more or less hypnotizable) found in numerous studies, predominantly on student populations, is representative of the general population has yet to be proven ( Peter and Roberts, 2022 ). For example, when using a shortened version of the HGSHS-5:G ( Riegel et al, 2021 ), which comprises only 5 instead of the 12 items of the HGSHS:A ( Shor and Orne, 1962 ) and thus appears to be significantly shorter and much more suitable for clinical studies, skewed score distributions were observed: a right skew (more high hypnotizables) in participants of a hypnosis congress ( Wolf et al, 2022 ), and a left skew (fewer high hypnotizables) in patients. These results are analyzed in more detail in another article in this Research Topic ( Zech et al, 2024 ).…”
Section: Hypnosis In Psychotherapy and Psychosomaticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Whether the normal distribution (10–25% highly hypnotizable, 10–25% low hypnotizable and the rest more or less hypnotizable) found in numerous studies, predominantly on student populations, is representative of the general population has yet to be proven ( Peter and Roberts, 2022 ). For example, when using a shortened version of the HGSHS-5:G ( Riegel et al, 2021 ), which comprises only 5 instead of the 12 items of the HGSHS:A ( Shor and Orne, 1962 ) and thus appears to be significantly shorter and much more suitable for clinical studies, skewed score distributions were observed: a right skew (more high hypnotizables) in participants of a hypnosis congress ( Wolf et al, 2022 ), and a left skew (fewer high hypnotizables) in patients. These results are analyzed in more detail in another article in this Research Topic ( Zech et al, 2024 ).…”
Section: Hypnosis In Psychotherapy and Psychosomaticsmentioning
confidence: 99%
“…However, "hypnophilic" people, i.e., people who are generally interested in hypnosis, show high levels of the schizotypal personality style, the more so the more hypnotizable they are (see also Jamieson and Gruzelier, 2001). A whole series of studies indicate that we can speak of a homo hypnoticus in this context (Peter et al, 2014;Peter and Böbel, 2020;Wolf et al, 2022;Peter and Wolf, 2023).…”
Section: Hypnotizabilitymentioning
confidence: 99%